STUDI ETNOGRAFI KOMUNIKASI DELL HYMES PADA GAYA KOMUNIKASI KOMUNITAS ROHANI SEL SANTUNNN - Shenthya Winarty (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the communication style within the spiritual community of Sel Santunnn by employing Dell Hymes' ethnography of communication approach through the SPEAKING model. Sel Santunnn, as part of the Nafiri Discipleship Church, exhibits unique interaction dynamics through a combination of verbal and nonverbal communication. This qualitative research involved seven community members as subjects, with data collected through in-depth interviews, participant observation, and documentation.The findings indicate that this community adopts a communication style characterized by cooperation, empathy, and dynamic expression. An informal atmosphere and interaction norms that encourage openness are key elements in strengthening interpersonal bonds and achieving collective goals, such as spiritual growth and group solidarity. The cooperative, animated, and friendly communication style practiced by this community contributes to the group's sustainability and harmony. These findings emphasize the importance of communication style in building an inclusive and supportive community.